Aktivitas Antiplasmodium in vivo fraksi N-butanol kulit batang Mahoni (Swietenia mahagoni) dan Asam Klorogenat - Lukmayani, Yani; Supriyatna, Supriyatna; P. S, Glorida; Muis, Abdul (UI Scholars Hub, 2011)
An antiplasmodial activity of n-butanol fraction from mahoni bark extract (Swietenia mahagoni Jacq.) and pure compound chlorogenic acid were investigated on white male miceSwiss derivated strain which were infected by Plasmodium berghei ANKA strain. Samplewere administrated i.p ., which n-butanol fraction with convertion dose 100, 200 and 400 mg/kgBW and chlorogenic acid with dose 0,01; 0,1; 1 and 10 mg/kg BW respectively for a period of 4days, consecutively started one day after parasit inoculation.Parasit persentage was counted daily (H0 to H4).The best aniplasmodial activity was shown by n-butanol fraction with convertion dose 200mg/kg BW (fraction dose 81,89 mg/ kg BW )with inhibition persentage 45.05% and chlorogenic acidwith dose 10 mg/kg BW with inhibition persentage 55,51%.